Liturgi Profetis Kesederhanaan: Studi Etika Ibadah Dan Penolakan Konsumerisme - Sumiyati Sumiyati (Ritornera - Jurnal Teologi Pentakosta Indonesia, 2025)
This article examines how liturgy can function as a prophetic voice that challenges the growing influence of consumerism within the life of the church. Recognizing that worship is never theologically or socially neutral, this study highlights the significance of simplicity as a core value that guides believers back to the essence of true worship. Employing a library research method, the study explores literature on liturgical theology, Christian ethics, and social analyses of consumerism’s impact. Through a hermeneutical approach, various theological insights are synthesized to formulate an understanding of prophetic liturgy rooted in simplicity. The discussion reveals that simple yet meaningful liturgical practices serve as a form of faith-based critique toward materialistic lifestyles, while nurturing an ethical consciousness that encourages believers to live with greater sensitivity, justice, and responsibility. The findings affirm that prophetic liturgy grounded in simplicity offers a relevant model for renewing worship amid the pressures of a consumer-driven culture.AbstrakArtikel ini menelaah bagaimana liturgi dapat berfungsi sebagai suara profetis yang menantang budaya konsumerisme yang semakin memengaruhi kehidupan gereja. Berangkat dari kesadaran bahwa ibadah tidak netral secara teologis maupun sosial, kajian ini menyoroti pentingnya kesederhanaan sebagai nilai inti yang mengarahkan umat kembali pada esensi penyembahan yang berpusat hanya kepada Allah. Penelitian ini menggunakan metode studi kepustakaan dengan menelusuri literatur teologi liturgi, etika Kristen, serta analisis sosial mengenai dampak konsumerisme. Melalui pendekatan hermeneutik, berbagai gagasan teologis diolah untuk merumuskan pemahaman tentang liturgi profetis kesederhanaan. Pembahasan menunjukkan bahwa liturgi yang sederhana namun bermakna mampu menjadi sarana kritik iman terhadap pola hidup materialistik, sekaligus membentuk kesadaran etis jemaat untuk hidup lebih peka, adil, dan bertanggung jawab. Hasil kajian menegaskan bahwa liturgi profetis kesederhanaan berpotensi menjadi model pembaruan ibadah yang relevan bagi gereja di tengah tekanan budaya konsumtif.